1989
DOI: 10.1111/j.1095-8649.1989.tb02986.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic reactions of rainbow trout, Salmo gairdneri Richardson, macrophages for larvae of the eye fluke Diplostomum spathaceum (Digenea)

Abstract: The killing ability of rainbrow trout macrophages for the infective larval stages of Dip/ostomum spnthaceum, cercariae and diplostomules. was investigated. Isolated macrophages kill significant numbers of diplostomules at effector : target ratios of 150 : 1 or greater. In v i m killing was not increased using antiserum-coated larvae or in vivo-activated macrophages individually, but when they were combined increased killed occurred. Diplostomules were capable of eliciting respiratory burst activity from macrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 51 publications
0
45
0
Order By: Relevance
“…not the parasite was opsonized with rainbow trout It is not known whether macrophages found in the serum. Similar colonization of helminths of the genera cephalic ducts were attracted to the mannose-rich Diplostomum and Sanguinicola by fish leucocytes were regions in this head organ as demonstrated by Buchreported by Whyte et al (1989) and Richards et al mann (1998) or if some other factors present in those (1996a), respectively. In addition, the presence of penstructures were responsible for macrophage attachtoneal macrophages in the incubation medium was ment.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…not the parasite was opsonized with rainbow trout It is not known whether macrophages found in the serum. Similar colonization of helminths of the genera cephalic ducts were attracted to the mannose-rich Diplostomum and Sanguinicola by fish leucocytes were regions in this head organ as demonstrated by Buchreported by Whyte et al (1989) and Richards et al mann (1998) or if some other factors present in those (1996a), respectively. In addition, the presence of penstructures were responsible for macrophage attachtoneal macrophages in the incubation medium was ment.…”
Section: Discussionmentioning
confidence: 58%
“…This would correspond The cytokine production by macrophages is also to the respiratory burst induction in rainbow trout likely to be of importance. It is suggested that the against other metazoan parasites, as shown for Diploneighbouring mucous cells proliferate (Balm et al stomum spathaceum (Whyte et al 1989) andDiphyl-1995) and secrete their products due to the release of 11-lobothnum dendriticum (Sharp et al 1991). 1 from macrophages (Cohan et al 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the in vitro killing of parasites by rainbow trout leucocytes suggest that reactive oxygen species (ROS) produced by the respiratory burst of macrophages evoked damage to the plerocercoid tegument of the cestode Diphyllobothrium dendriticum (Sharp et al 1991) and killed the digenean, eye-fluke Diplostomum spathaceum (Whyte et al 1989). Whyte et al (1989) discussed the issue that the increased contact between macrophages and a parasite ensures the release of ROS and lytic enzymes, causing direct damage to the parasite. Hamers et al (1992) suggested carp granulocytes caused damage to the metasoma tegument of Paratenuisentis ambiguus by the release of granule contents.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, there have been a limited number of investigations of the interaction between the fish complement system and metazoan parasites. Studies by Whyte, Chappell & Secombes (1989, 1990 revealed that the immune protection mechanism in rainbow trout against the eye-fluke Diplostomum spathaceum involved both the alternative and classical pathways of complement activation. In studies by Buchmann (1998) it was also noted that the lethal effect of plasma from Oncorhynchus mykiss on the monogenean Gyrodactylus derjavini was mediated through the binding of complement factor C3 to carbohydrate-rich parasite structures.…”
Section: Introductionmentioning
confidence: 99%